Pengaruh Sosialisasi Standar Operasional Prosedur Pengisian International Certificate Of Vaccination Terhadap Kemampuan Perawat Dalam Pengisian International Certificate Of Vaccination Di Poliklinik Rumah Sakit Haji Jakarta Tahun 2023 - Almudiawati Almudiawati; Marisca Agustina; Ahmad Rizal (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Introduction: International Certificate of Vaccination (ICV) is an official international document issued by the Port Health Office as the agency with authority to prevent the entry and exit of infectious diseases from Indonesia to other countries or vice versa, as proof that a person has received certain vaccinations. Socialization is a social process where an individual develops attitudes to behave in accordance with the behavior of the people around him. In filling out and giving the International Certificate of Vaccination (ICV) the skills of polyclinic nurses at the Haji Hospital Jakarta are needed. For this reason, researchers see the need to hold a socialization of operational standards for filling out the International Certificate of Vaccination (ICV) regarding the ability of nurses to fill out the International Certificate of Vaccination (ICV) at the Jakarta Hajj Hospital Polyclinic in 2023. Objective: This research is to determine the ability of nurses to fill out International Certificate of Vaccination (ICV) in accordance with the International Certificate of Vaccination (ICV) Standard Operational Procedures Research Method: This method uses a quasi-experimental design with a pretest-posttest design type. Data collection methods include the use of observation sheets to measure nurses' abilities before and after the intervention. Socialization of Standard Operational Procedures for Filling Out the International Certificate of Vaccination (ICV). This study aims to assess the influence of Socialization of Standard Operational Procedures for Filling Out the International Certificate of Vaccination (ICV) on Nurses' Ability to Fill Out International Certificate of Vaccination (ICV) at the Jakarta Hajj Hospital Polyclinic in 2023. Results: Based on the results of statistical tests using the Paired Samples Test, the p value obtained was p 0.001<0.05, meaning there was a significant difference or influence between the abilities of nurses after carrying out the Socialization Standards. Operational Procedures for Completing the International Vaccination Certificate (ICV). Conclusion: The conclusion of the research is that there is an influence of the socialization of standard operational procedures for filling out the International Certificate of Vaccination (ICV) on the ability of nurses to fill out the International Certificate of Vaccination (ICV) in the polyclinic at Haji Hospital Jakarta.